(untitled) (Research, Society and Development, 2022)
Medical education, as a result of the pandemic, went through several adaptations quickly to build online education. The purpose of this article is to outline reflections for the construction of support points for the possible gaps existing in that period. This is an experience report from the perspective of Comprehensive Health Care teaching assistance about medical education and its contributions to fighting the pandemic at the Federal University of Pará, in the first two years of the Medicine Course. Google Meet tool and videos were the most used means in the emerging scenario of the pandemic, in which teaching assistance was present, acting in support to students and teachers and helping in the management of digital tools and in the construction of the evaluation of the learning process. Monitoring the medical education provided during the pandemic period is necessary, as theoretical and practical shortages may have occurred. Therefore, alternatives must be implemented, such as carrying out simulations and/or retrograde content evaluations, in order to fill these possible gaps.